A tale of the financial inclusion-growth nexus and the degree of financial inclusion: a dynamic panel approach on selected developing countries. Issue 3 (26th July 2021) - Nandi, Biplob Kumar; Hasan, Gazi Quamrul; Kabir, Md. Humayun
Abstract : Purpose: This study aims to examine the impact of financial inclusion on per capita gross domestic product (GDP) at varying degrees of financial inclusion for a sample of 76 developing countries between 2011 and 2017. To evaluate the heterogeneous impact, this paper constructs the multi-dimension index of financial inclusion to classify sample countries into two sub-samples in terms of the value of FIID, taking account of three dimensions of financial inclusion: access, usage and availability. Design/methodology/approach: This study attempts to identify the presence of reverse causality and long-run relationship between financial inclusion and economic growth by using the Granger causality test (Wald test) and three alternative panel cointegration tests (Kao Test, Pedroni Test, Westerlund Test) respectively. Because of the existence of the bi-directional causality between financial inclusion and per capita GDP, this study uses a fixed effect instrumental variable model with lagged dependent variable to get unbiased estimators from the panel regressions for sample countries. Findings: This paper finds a strong positive impact of financial inclusion on per capita GDP growth in sample developing countries, controlling for labor market structure, financial institutions' efficacy, infrastructural and governance issues. This study suggests that economic growth will be high in developing economies with a higher level of financial inclusion; however, the positive impact for two sub-samples countries (low and medium level of inclusion and high level of inclusion) are heterogeneous. The estimated result explains that a 1% increase in the financial inclusion index leads to a 0.0153% point increase in the per capita GDP for the countries with a low and medium level of financial inclusion, while this positive impact is significantly higher, 0.0794% point for countries with the high level of financial inclusion. This study also suggests that the higher concentration in the financial market by few agents and the lower level of governance may have an adverse impact on economic growth for the economies with a low and medium level of financial inclusion. Originality/value: This study is an original study that contributes to the research gap by explaining the heterogeneous impact of financial inclusion on economic growth at varying degrees of inclusion in the two sub-sample countries. Moreover, this study posits greater appeal as it explores the issue using the sample of only developing economies.